Women's Health Crisis in Pakistan - Zafar Mirza (Journal of University College of Medicine and Dentistry)
This editorial highlights the critical health crisis faced by women in Pakistan, affecting nearly 120.7 million citizens. Gender inequality, poor reproductive healthcare, and systemic neglect contribute to the widespread health challenges women face throughout their life course. Key issues include high rates of malnutrition, anemia, undernourishment, and a high fertility rate, with significant disparities in rural areas. Women also face a heightened risk of communicable and non-communicable diseases, including the highest breast cancer rate in Asia. Economic factors, such as low workforce participation and wage gaps, further exacerbate these challenges. The editorial calls for comprehensive healthcare reforms focused on governance, financing, and addressing gender biases to improve women’s health and create a more equitable healthcare system. Addressing these disparities is essential for empowering women and enhancing their well-being.